A single vector system for tunable and homogeneous dual gene expression in Escherichia coli - Z. Živič; L. Lipoglavšek; J. Lah; S. Hadži (Scientific Reports)
Abstract Expression of recombinant genes can be controlled using inducible promoters. However, the most commonly used IPTG- and arabinose-inducible promoters result in an ‘all-or-nothing’ response, leading to fully induced and uninduced bacterial subpopulations. Here, we investigate whether appropriate modifications to these promoter systems can be combined into a single vector system, enabling homogenous expression of two genes of interest that can be precisely tuned using inducer concentration. We show that modifications of positive feedback loops related to inducer uptake result in homogeneous gene expression in both the T7 lactose and pBAD arabinose systems. Furthermore, these two modified systems were combined into a single vector, pRAT-sfGFP that provides the desired tunable expression of two genes of interest. Finally, we test this single-vector system as a tool for studying two-component genetic circuits, using toxin-antitoxin modules as model systems. This novel low-copy single vector expression system opens up new possibilities for investigating the function of two-component bacterial genetic circuits.